Phylogeny and chromosomal diversification in the Dichroplus elongatus species group (Orthoptera, Melanoplinae) - Castillo, Elio R.D.; Taffarel, Alberto; Maronna, Maximiliano M.; Cigliano, María Marta; Palacios-Gimenez, Octavio M. [UNESP]; Cabral-De-Mello, Diogo C. [UNESP]; Martí, Dardo A. (Public Library of Science (PLoS), 2017)
In an attempt to track the chromosomal differentiation in the Dichroplus elongatus species group, we analyzed the karyotypes of four species with classical cytogenetic and mapping several multigene families through fluorescent in situ hybridization (FISH). We improved the taxon sampling of the D. elongatus species group adding new molecular data to infer the phylogeny of the genus and reconstruct the karyotype evolution. Our molecular analyses recovered a fully resolved tree with no evidence for the monophyly of Dichroplus. However, we recovered several stable clades within the genus, including the D. elongatus species group, under the different strategies of tree analyses (Maximum Parsimony and Maximum Likelihood). The chromosomal data revealed minor variation in the D. elongatus species group's karyotypes caused by chromosome rearrangements compared to the phylogenetically related D. maculipennis species group. The karyotypes of D. intermedius and D. exilis described herein showed the standard characteristics found in most Dichroplini, 2n = 23/24, X0♂ XX♀, Fundamental number (FN) = 23/24. However, we noticed two established pericentric inversions in D. intermedius karyotype, raising the FN to 27♂/28♀. A strong variation in the heterochromatic blocks distribution was evidenced at interespecific level. The multigene families' mapping revealed significant variation, mainly in rDNA clusters. These variations are probably caused by micro chromosomal changes, such as movement of transposable elements (TEs) and ectopic recombination. These observations suggest a high genomic dynamism for these repetitive DNA sequences in related species. The reconstruction of the chromosome character variation in the FN posits the FN = 23/24 as the ancestral state, and it is hypothesized that variations due to pericentric inversions has arisen independently three times in the evolutionary history of Dichroplus. One of these independent events occurred in the D. elongatus species group, where D. intermedius is the unique case with the highest FN described in the tribe Dichroplini.